Analysis of trends in extreme flood events and mitigation strategies in SOUTHEAST ASIA. [Abstract only]. - Amarnath, Giriraj; Pavelic, Paul; Smakhtin, Vladimir U. (2013)
Floods are one of the most frequent and widespread natural hazards in the world. A recent example is the 2011 floods in three of the four Lower Mekong Basin Countries (Thailand, Cambodia and Vietnam) that caused severe impacts in terms of loss of life and damage to infrastructure. Several studies have highlighted the increasing importance of developing spatio-temporal flood hazard databases to understand flood dynamics more systematically at a range of spatial scales within SOUTHEAST ASIA (SEA). This study is proceeding on two distinct fronts: the first focusses on ranking and prioritization of impacts across SEA, whilst the other examines an approach to flood monitoring that evaluates the feasibility of implementing possible mitigation strategies that still provide for the degree of flow variability needed to maintain ecosystems. Firstly, long-term time-series data from multiple sources (e.g. EM-DAT, DFO, Sentinel Asia) was used in identifying flood hotspots including their frequency, intensity/severity and societal impacts. This will also help in evaluating and improving hydrological modeling predictions and provide better information for more effective flood hazard, flood risk and preparedness studies. Flood hotspots were further investigated taking into account of agricultural extent loss, populations at risk and economic loss. The results from the hotspot analysis suggest more climate risk investments are needed to minimize risk and are likely to have the biggest payoff in terms of reduced losses. The nature of those investments and the associated cost-benefits are being revealed. Secondly, a new approach is being developed for flood monitoring from time-series MODIS data acquired from 2000 to 2012. This approach will help in identifying basin to regional-scale temporal changes in inundated area; duration of inundation cycles between large-medium-small scale floods. Thus satellite-based mapping of flood risks areas will help in identifying prospective areas for floodwater harvesting in the upstream areas to reduce negative impacts downstream.